PENERAPAN MODEL PjBL (PROJECT BASED LEARNING) TERHADAP KEMAMPUAN LITERASI SAINS DAN SIKAP ILMIAH PESERTA DIDIK SMA KELAS X PADA MATERI BIOTEKNOLOGI - Risa Indriani; Indra Dodo Saputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of students’ scientific literacy and scientific attitudes in Biology learning, particularly on Biotechnology material. This study aimed to analyze the students’ initial abilities, improvement, and the effectiveness of the implementation of the Project Based Learning (PjBL) model on scientific literacy and scientific attitudes. The study employed a pre-experimental method with a one group pretest-posttest design. The research was conducted at SMAN 18 Garut in class X-10 during the second semester of the 2025/2026 academic year with a sample of 30 students selected using cluster random sampling technique. The research instruments consisted of essay tests on scientific literacy and scientific attitude questionnaires. Data were analyzed using Shapiro-Wilk normality test, paired sample t-test, N-Gain, and Cohen’s d effect size with SPSS version 26. The results showed that the average scientific literacy score increased from 48.00 to 70.31, while scientific attitude increased from 72.24 to 83.37. The paired sample t-test showed a significance value of 0.000 < 0.05, indicating a significant improvement after treatment. The N-Gain results for scientific literacy and scientific attitude were 0.41 and 0.42 respectively, both categorized as moderate. The effect size results were categorized as very large. Therefore, the implementation of the Project Based Learning (PjBL) model was effective in improving students’ scientific literacy and scientific attitudes on Biotechnology material.